Spittlebugs (Hemiptera: Cercopidae): Integrated pest management on gramineous crops in the Neotropical Ecozone - Espitia, Paula A.; Manzano, María R.; Hernández, Luis Miguel (Frontiers Media, 2022)
Spittlebug (Hemiptera: Cercopidae) species cause large economic losses on gramineous crops (Poaceae) in tropical and subtropical America. These insects are key pests of sugarcane and forages, crops that experienced a quick expansion in extensive monocultures in Brazil, Colombia, and Mexico. Mobilization toward sustainable crop and livestock systems to supply the growing demand of meat, milk, and sugar in Latin America and the Caribbean region implies developing sustainable and feasible strategies of integrated pest management to control spittlebugs. This review combines information on Cercopidae taxonomy, geographical distribution, insect biology, and control strategies to contribute to the development of integrated pest management in grasses and sugarcane in the Neotropics.